Dynamic influence of screening coals on a vibrating screen. (15th March 2018) - Peng, Liping; Wang, Zhenqian; Ma, Wenda; Chen, Xihui; Zhao, Yuemin; Liu, Chusheng
Graphical abstract: Highlights: The screening coals make the screen structure experience an enhanced random vibration. The discovered additional random vibration in the screening process is analyzed to be stable and ergodic. Statistical characteristics of the random vibration change along with the screening capacity. The discovered dynamic characteristics can be applied into analyzing mechanics characteristic the bearing beam. Abstract: Screening is an indispensable unit operation in coal preparation. Coals often cause structural damage of a large vibrating screen during large-scale screening process. In this paper, structural vibration and strain signal of a vibrating screen were tested and analyzed for investigating the dynamic influence of screening coals on the vibrating screen. Several experiments were conducted with the empty-load operation and screening process of two different screening capacities. The obtained fundamental vibration characteristic indicated that the screening coals made the screen structure experience an enhanced vibration for the discovered additional random vibration, and the structural strain increased by 14.79% to improves the possibility of structural damage. Aiming at the emerging random vibration, a stationary test and ergodicity test were adopted for analyzing the captured vibration signal. The results demonstrated that random vibration of the vibrating screen was stable and ergodic, which means that any section of the captured signal is enough to be analyzed for representing the vibration properties of the whole screening process. Additionally, statistical characteristics of the random vibration also changed along with the screening capacity. Eventually, these new dynamic characteristics were applied into analyzing mechanics characteristic of the bearing beam theoretically and the maximum error is within 14%, while the error can reach up to 40% in a traditional calculation method without influence of screen coals considered.